PENGARUH HARGA TERHADAP KEPUTUSAN SISWA SMA MUHAMMADIYAH 1 PALEMBANG DALAM MEMBELI PONSEL BLACKBERRY CURVE (Studi Kasus) - Yusnizal Firdaus; Nirwan Rasyid (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
The Purpose of this research is to determine the effect of price against the decisions of consumers in purchasing BlackBerry Curve at Senior High School students at  Muhammadiyah 1 Palembang.  The writer would like to know how prices affect students’ decisions to buy the BlackBerry Curve.  Data used is the purchase decision, which is the dependent variable (Y) and the influence of price is the independent variable (X).  Quantitative method was used in this research, in taking the samples, the writer used the stratified random sampling technique.  95 samples were asked to complete the questionnaire.  The obtained data were processed by using sloven's formula as quoted by Husein (2001) then those data were analyzed by using the theoretical framework developed by private (2011).  The writer found that there was price effect against students' decisions to buy the BlackBerry Curve.  The result showed that the coefficient regression value was 0,611 it meant that there was a positive correlation between price affect against students' decisions to buy the BlackBerry Curve. Based on the value above, the writer can conclude that any value addition carried a price variable, then an increase in students purchasing decision to buy a BlackBerry Curve.